The Role of Technology in The Transformation of Accounting Financial Audit Case Study of Blockchain Implementation in The Audit Process - Lifaldi, Bahri; Hasanudin, Agus Ismaya; Ismawati, Iis (Journal of Applied Business, Taxation and Economics Research, 2024)
With the increasing number of cyber attacks and data security breaches, the protection of financial information is becoming increasingly important. Conventional financial audit systems may not have adequate mechanisms to protect sensitive data from the rapidly evolving digital security threats. The aim of this research is to determine the role of technology, particularly blockchain technology, in transforming the financial audit process in accounting practice, and to understand the impact of implementing blockchain technology in the financial audit process on the efficiency, transparency, and accuracy of financial information. The research method used in this study is a Systematic Literature Review (SLR). The results of this study indicate that the use of blockchain technology in financial audit practice provides an effective solution for improving the integrity, reliability, and quality of financial reports presented by companies. Keywords: technology, financial audit, blockchain